CSO secret communication. Issue 25 (1st December 2019) - Yan, Senlin
Abstract : A chaos shift parameter synchronisation (CSPS) system based on two different mutually coupled lasers synchronising with another laser is studied while a novel chaos shift orbit (CSO) encoding technique is presented for secret communication. CSPS between the emitter and receiver can still be obtained by shifting the emitter's parameter in real time, where the emitter operates its chaos to vary its orbit or jump across its orbit by using real‐time current changes of one laser. Then, a CSO encoding scheme is implemented successfully. The emitter has numerous real‐time shifting secret keys, so it is highly secure, and the signal is difficult to decipher.